Extensive and functional overlap of the STAT6 and RXR cistromes in the active enhancer repertoire of human CD14+ monocyte derived differentiating macrophages. (15th August 2018) - Czimmerer, Zsolt; Nagy, Zsuzsanna S.; Nagy, Gergely; Horvath, Attila; Silye-Cseh, Timea; Kriston, Agnes; Jonas, David; Sauer, Sascha; Steiner, Laszlo; Daniel, Bence; Deleuze, Jean-Francois; Nagy, Laszlo
Abstract: Macrophages are able to differentiate into classically polarized (M1) or alternatively polarized (M2) states upon encountering pro-inflammatory cytokines such as interferon (IFN) γ or anti-inflammatory cytokines such as interleukin (IL) -4/IL-13, respectively. Moreover, macrophages are known to regulate lipid metabolism via multiple members of the nuclear hormone receptor family, including the retinoid X receptors (RXR). It has been also documented that cytokines are able to modulate macrophage responses to lipid signals but the nature of these interactions and the underlying mechanisms of these processes especially at the level of the chromatinized genome are not well understood. Previous work from our laboratory suggested that STAT6 is a facilitator of nuclear receptor mediated transcriptional activity acting at the genome level. This prompted us to investigate genome-wide DNA binding events and the development of cistromes in human CD14+ monocyte-derived macrophages upon exposure to IL-4. We determined the impact of IL-4 on the PU.1, RXR and STAT6 cistromes within the active enhancer regions marked by H3K27-acetylation using chromatin immunoprecipitation followed by deep sequencing and integrated bioinformatics analyses. We found that about 2/3rd of the IL-4 induced STAT6 peaks co-localized with RXR peaks. These STAT6/RXR co-peaks differed at least in part from the non-overlapping RXR peaks regarding the most enriched de novo transcription factor binding motifs. Interestingly, RXR-binding was not regulated at the STAT6/RXR co-bound enhancers following IL-4 stimulation, but differential enhancer interactions were observed between the IL-4/STAT6 and RXR signaling pathways acting in a gene selective manner. Our results suggest that there is a novel, so far uncharacterized cistromic crosstalk between RXR and STAT6 that is likely to contribute to the formation of the active enhancer repertoire, transcriptome and differential signal-specific gene regulation of polarized macrophages. Highlights: Extensive overlap between IL-4-activated STAT6 and lipid sensing RXR cistromes in human differentiating macrophages. RXR/STAT6 co-peaks are associated with IL-4 responsive genes. Combined activation of STAT6 and RXRs lead to the complex crosstalk at gene and enhancer level enhancing IL-4 responsiveness.